Determinação do ponto de colheita e avaliação da pós-colheita de banana Princesa utilizando biofilme - Sarmento, Claudia Andrade Ribeiro (2012)
The objective of this study was develop a protocol to determine an ideal point to harvest the fruits of: Banana Princesa using the aborted bracts method, also studying their physical and chemical characteristics and extend the postharvest life of fruits using starch and chitosan biofilms. In determining the point of harvesting the fruit, the banana of BRS Princesa variety were obtained at the Jorge Prado Sobral Experimental Camp of Embrapa Coastal Tablelands in Nossa Senhora das Dores -SE. The fruits were selected according to the number of aborted bracts from the is suance of the inflorescence to the time of harvest, resulting in clusters with 90, 95, 100 and 105 aborted bracts. The physical and chemical analysis were performed every 3 days in the fruits of 2nd and 3rdclusters: soluble solids, titratable acidity, loss of mass, length and diameter of fruits, pH, firmness, peel color and activity of the pectinmethylesterase enzyme. The experimental design was completely randomized in factorial scheme 4x5, with 4 points of harvest and 5 periods of analysis. The results were evaluated statistically by ANOVA and Tukey test (p <0.05), using the statistical program SISVAR. For all physical and chemical parameters analyzed, the fruits harvested with 90aborted bracts had an acceleration in their metabolism compared with other treatments, once the fruits harvested at 95 and 100 aborted bracts had the best physical and chemical characteristics to be adopted as optimal point of harvest for the Banana Princesa variety, since it presented a good increase insoluble solids, similar values of titratable acidity, a small firmness of this fruits until the endof the experiment, small enzymatic activity of PME, maturation indexand pHsimilar, lower rates ofmass lossand bestvaluesfor the parameters of peel color,L*, C*and h°.However it will be adopted the fruitwith 95bractsaborted to be the ideal point of harvested, once it is soon. In the second part of the work, the fruit came from the same orchard and the same physical and chemical analysis were performed in the fruits of 2nd and 3rd with 95 bracts aborted. . The experimental design was completely randomized in factorial scheme (5x4), with 5 coutings and 4 periods of analysis, and results were evaluated statistically by ANOVA and Tukey test (p <0.05), using the statistical program SISVAR. As seen in all physical and chemical analysis the treatment of the starch and chitosan by 4% accelerated metabolism of the fruit, reducing their shelf life. The fruits submitted to the starch biofilm by 2%, presents the best results in physical and chemical analysis as to the postharvest preservation of fruits, because it presented an increase in their valuesof soluble solids only at the end of the experiment, reaching values similar in titratable acidity during the experiment, the fruits remained firmer than the other treatments, had lower activity of the enzyme pectinmethilesterase, maturation index values and pH similar, lower mass loss and better values for the parameters of peel color, L*, C*and h°.